Antocianina obtida de fruto de Palmeira Juçara (Euterpe edulis mart.) : estabilização com aplicação em alimentos - Passos, Ana Paula da Silva dos (2011)
Anthocyanins are naturally phenolic compounds occurring in plants and have functional characteristics that exert beneficial health effects. They can be used as natural food colorants, but are unstable in some technological processes. The microencapsulation technique is a promising option for the stabilization of pigments, in which the sensitive compounds are encapsulated by a coating material or wall protecting them from factors that may cause their deterioration by light, oxygen and others. This study was aimed at the extraction and quantification of total anthocyanins found in fruit pulp of Euterpe edulis Mart. (Palm Juçara) and its subsequent stabilization by the microencapsulation technique with maltodextrin DE20 by lyophilization. The extraction of anthocyanins was carried out with a solution of ethanol / water ratio of 7:3 and subsequently the extract was evaporated, frozen in liquid nitrogen and lyophilized. The extract was quantified by the pH differential method, which consists of using two buffer systems, one with potassium chloride at pH 1.0 and 0.025 M and the other with sodium acetate at pH 4.5 and 0.4 M. The microencapsulation with 1 g of freeze-dried extract in 10 DE20 g of maltodextrin (1:10) was performed. The process yield, calculated as the difference between the compounds on the surface of the capsules and the encapsulated theoretically. The tests to verify the effect of heat treatment and pH, respectively, were made at different time / temperature and pH / time. The morphological evaluation of microencapsulated compounds was performed using a scanning electron microscope. Thermal analysis of differential scanning calorimetry (DSC), thermogravimetry (TG) and photoacoustic analysis, respectively, were made to evaluate the interaction of maltodextrin and microencapsulated extract, mass loss and the intensity of light that was absorbed by the sample. The powders were added in yogurts and the sensory and colorimetric characteristics were studied in order to compare the plain yogurt formulations with pure and microencapsulated colorant. The resulting lyophilized extract showed intense pink color, and content of 14340.2 mg. L-1 of total anthocyanins and 93.6% of microencapsulation yield. The effect of temperature has shown that the maltodextrin DE20 gave protection to 70 ° C for 120 min. The pH in which the red color predominated was 1.5 to 5.0, because as PH increases the anthocyanins change their conformation and, consequently, lose their particular color. The morphology of particles were observed using a a scanning electron microscope and showed morphology with smooth surface flakes. The conformation shown is a feature of the lyophilization process and distinguish itself from other routine processes, such as "spray dryer" in which the particles are relatively uniform and spherical. Among the advantages of freeze drying, is the use of low temperature for drying and resulting in the preservation of thermosensitive compounds. DSC and TG analysis showed that there was weak interaction between the samples and the encapsulating agent and photoacoustic has shown the sensitivity of the array facing the light. The yogurts added of pure and encapsulated anthocyanin had a pink color, which approached the red for the instrumental analysis. The notes on sensory analysis ranged from "slightly liked" to "liked very much", and purchase intent for all formulations was above 50%. Therefore, it was possible to perform the extraction, quantification, microencapsulation, thermal stabilization and pH and food application of anthocyanins found within the pulp of the fruits of Euterpe edulis Mart. (Palm Juçara).